Lead levels and cognitive abilities in Peruvian children - Vega-Dienstmaier, Johann (2006)
Objective: To study the relationship between blood lead levels and cognitive abilities of children exposed to this metal. Method: This is a cross-sectional study that included 134 children aged 6 to 8.5 years old from 3 schools with different risks of lead exposure located in El Callao (Peru). Cognitive assessments were made by means of the Graphic Test of Reasoning (GTR) and the Kohs Block Design Test (KBDT). Blood lead levels and other laboratory tests were performed. Results: Children with lead > 10 ug/dl presented greater prevalence of low scores in the Graphic Test of Reasoning (18.9% vs. 7.1%, p = 0.049) and in the Kohs Block Design Test (KBDT) (39.6% vs. 18.6%, p = 0.01) compared with those with lower lead blood levels. A deficit of 1 category in the Graphic Test of Reasoning was associated with an increase in lead blood level of 16.78 ug/dl (assuming a linear relationship) and from 1 to 5.19 ug/dl (logarithmic model). For each 10 ug/dl of increase in lead levels, the Kohs Block Design Test decreases in 6.24 units (12.91 in males and 0.216 in females) (linear model), and an increase from 1 to 10 ug/dl corresponds to a drop of 16.44 points in the Kohs Block Design Test (31.19 in males and 3.98 in females) (logarithmic model). Considering the Graphic Test of Reasoning subscales, lead levels correlated negatively with the areas of numerical problems (rho = -0.445, p < 0.001), numerical relationships (rho = -0.365, p < 0.001), inferences (rho = -0.281, p = 0.002) and similarities (rho = -0.250, p = 0.005). Conclusions: Lead levels were non-linearly associated with lower cognitive abilities, especially in males, being the numerical reasoning the most affected area.